2020
DOI: 10.1017/s0140525x19003182
|View full text |Cite|
|
Sign up to set email alerts
|

Language as a mental travel guide

Abstract: Gilead et al.'s approach to human cognition places abstraction and prediction at the heart of “mental travel” under a “representational diversity” perspective that embraces foundational concepts in cognitive science. But, it gives insufficient credit to the possibility that the process of abstraction produces a gradient, and underestimates the importance of a highly influential domain in predictive cognition: language, and related, the emergence of experientially based structure through time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…There was an editorial error in the original online version of the commentary by Davis et al (2020) on the target article by Gilead et al (2020). The following sentence, "Importantly, and unlike Gilead et al's framework, which have since been shown, in deep recurrent neural networks, are general principles of learning and development (Elman et al 1996)."…”
mentioning
confidence: 99%
“…There was an editorial error in the original online version of the commentary by Davis et al (2020) on the target article by Gilead et al (2020). The following sentence, "Importantly, and unlike Gilead et al's framework, which have since been shown, in deep recurrent neural networks, are general principles of learning and development (Elman et al 1996)."…”
mentioning
confidence: 99%